Amorphous oxygen-deficient strontium titanate, preparation method thereof and application of amorphous oxygen-deficient strontium titanate in photocatalytic degradation of tetracycline

By introducing transition metal indium or zinc into strontium titanate, amorphous oxygen-deficient strontium titanate with high specific surface area, high performance and high stability is prepared, and the problem of low degradation efficiency of strontium titanate catalyst in the prior art is solved. It has achieved efficient and low-consumption tetracycline wastewater treatment and has good industrial prospects.

CN119160932APending Publication Date: 2024-12-20SHANGQIU NORMAL UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202410486376.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-22
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

There is a lack of efficient and low-consumption photocatalysts in the prior art for degrading tetracycline wastewater, especially in the amorphous form of strontium titanate catalysts.

Method used

By introducing transition metal indium or zinc in the preparation process of strontium titanate, changing its nucleation and growth process, amorphous oxygen-deficient strontium titanate with high specific surface area, high performance and high stability was prepared, and hydrothermal method was used. Perform preparation.

Benefits of technology

It improves the photocatalytic activity and structural stability of strontium titanate, significantly improves the degradation efficiency of tetracycline, has the advantages of green, environmentally friendly and low consumption, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses amorphous oxygen-deficient strontium titanate and a preparation method and application thereof.The preparation method includes the steps that isopropyl titanate is dissolved in ethylene glycol, and a solution A is obtained; dissolving strontium acetate and indium nitrate or zinc acetate in deionized water to obtain a solution B; and under magnetic stirring, dropwise adding the solution A into the solution B, stirring until the solution is uniformly dispersed, adding NaOH into the solution, stirring until the NaOH is completely dissolved, carrying out hydrothermal reaction, cooling to room temperature, cleaning and drying. The amorphous oxygen-deficient strontium titanate catalyst with high specific surface area, high performance and high stability is prepared by a hydrothermal method. The introduction of indium or zinc interferes with the nucleation and growth process of strontium titanate, and abundant surface defects are formed on the surface of strontium titanate, so that more reaction active sites are provided for photocatalytic reaction; the specific surface area and the carrier transport performance of strontium titanate are improved, and the adsorption capacity of the catalyst to antibiotics is enhanced; the amorphous design ensures that strontium titanate has a good structure and photocatalytic stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalysts, and specifically relates to an amorphous oxygen-deficient strontium titanate and a preparation method thereof and an application thereof in photocatalytic degradation of tetracycline.

[0002] The present invention belongs to the 3.1 New Functional Materials Industry Key Direction under 3.1.12 New Catalytic Materials and Additives, New Photocatalytic Materials and Other Additives in the 3 New Materials Industry of the Catalogue of Strategic New Industries. Background Art

[0003] Environmental pollution is a major challenge facing the world today, especially in terms of water pollution. As a common antibiotic, tetracycline wastewater treatment has always been a difficult problem in the field of environmental protection. As an emerging solar energy utilization technology, photocatalytic technology has shown unique advantages in treating low-concentration tetracycline wastewater. First of all, photocatalytic technology uses solar energy as a driving force and is green and environmentally friendly. In the photocatalytic process, the photocatalyst absorbs light energy to generate electrons and holes, which in turn triggers a redox reaction and decomposes tetracycline molecules into harmless small molecules. This process does not require the addition of any chemical reagents, so no secondary pollution will be generated. Secondly, photocatalytic technology has a significant effect on the treatment of low-concentration tetracycline wastewater. Due to the high efficiency and thoroughness of the photocatalytic reaction, even if the concentration of tetracycline is low, it can be effectively degraded through photocatalytic technology. In addition, photocatalytic technology also has the advantages of simple operation and low energy consumption. Compared with traditional physical and chemical treatment methods, photocatalytic technology does not require complex equipment and operation processes, which reduces the treatment cost. At the same time, since the photocatalytic reaction is carried out at normal temperature and pressure, the energy consumption is low, which is conducive to energy conservation and emission reduction. The development of high-efficiency and low-consumption photocatalysts is currently the focus of scholars' research.

[0004] In recent years, amorphous photocatalysts have attracted much attention due to their advantages of mild reaction conditions, high stability and abundant active sites. Amorphous materials generally have different physical and chemical properties from crystalline materials. They may have a higher degree of disorder, resulting in enhanced scattering of electrons and phonons, thus affecting their physical and chemical properties. In addition, amorphous materials may also have abundant surface defects, which make them have special applications in catalysis or chemical reactions. For example, amorphous CoMoS4 nanosheets have been used for photocatalytic hydrogen production, degradation of p-nitrobenzene and MB adsorption. In addition, there is an amorphous photocatalyst Co4I3O 24 H 15 3H2O, which has a significant photocatalytic degradation effect on organic dye pollutants when irradiated with visible light at room temperature.

[0005] Among many photocatalysts, strontium titanate has attracted extensive attention in the field of photocatalytic degradation due to its suitable band gap structure and abundant raw material reserves. Compared with strontium titanate crystals, amorphous oxygen-deficient strontium titanate has a higher number of surface active sites. This makes amorphous oxygen-deficient strontium titanate photocatalysts have broad application prospects in the photocatalytic degradation of organic pollutants. In addition, amorphous oxygen-deficient strontium titanate photocatalysts also have good stability and durability. It can maintain high catalytic activity under long-term illumination and is not prone to deactivation or structural damage. Moreover, the preparation method of amorphous oxygen-deficient strontium titanate photocatalyst is relatively simple and low in cost, which makes it more economical and practical in large-scale production and application. However, there are no reports on the design of amorphous oxygen-deficient strontium titanate. Summary of the invention

[0006] In view of the above problems existing in the prior art, the present invention adds transition metal indium or zinc into the preparation process of strontium titanate, changes the nucleation and growth process of strontium titanate, introduces defect sites, and improves the photocatalytic activity of strontium titanate, thereby providing an amorphous oxygen-deficient strontium titanate with high specific surface area, high performance and high stability, and a preparation method thereof, as well as an application in photocatalytic degradation of tetracycline.

[0007] The object of the present invention is achieved in the following manner: a method for preparing amorphous oxygen-deficient strontium titanate, specifically comprising the following steps: first, dissolving 1.0 mL of isopropyl titanate in 15-35 mL of ethylene glycol to obtain solution A; then dissolving 3.9 mmol of strontium acetate and 1-4 mmol of indium nitrate or zinc acetate in 15-35 mL of deionized water to obtain solution B; then, under magnetic stirring, adding solution A dropwise into solution B, stirring until solution A is uniformly dispersed in solution B, adding 0.10-0.30 g of NaOH into the above solution, stirring until it is completely dissolved, and then placing the mixed solution in a reactor for hydrothermal treatment at 160-180° C. for 6-20 h, then cooling to room temperature, and washing and drying.

[0008] When indium nitrate or zinc acetate is not evenly dispersed or NaOH is not fully dissolved, ultrasonic treatment is performed for 10 to 90 min.

[0009] The drying temperature is 60~80℃.

[0010] Cleaning is done by alternating between deionized water and ethanol 2 to 3 times.

[0011] Amorphous oxygen-deficient strontium titanate is prepared by the method.

[0012] Application of amorphous oxygen-deficient strontium titanate: amorphous oxygen-deficient strontium titanate is used for photocatalytic degradation of tetracycline.

[0013] Compared with the prior art, the present invention successfully prepares amorphous oxygen-defective strontium titanate catalyst with high specific surface area, high performance and high stability through a simple hydrothermal method. The operation is simple and the performance is excellent. The introduction of indium or zinc interferes with the nucleation and growth process of strontium titanate, thereby causing the following effects: (1) abundant surface defects are created on the surface of strontium titanate, which provides more reactive sites for photocatalytic reactions; (2) the specific surface area and carrier transport performance of strontium titanate are improved, and the adsorption capacity of the catalyst for antibiotics is enhanced; (3) the amorphous design ensures that strontium titanate has good structure and photocatalytic stability. Therefore, compared with strontium titanate crystals, the photocatalytic tetracycline degradation performance is significantly improved, the catalyst has good structural stability, and has the advantages of being green, environmentally friendly, low-consumption, high-efficiency and having good industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 These are XRD, transmission electron microscope and selected area electron diffraction photos of the strontium titanate crystal prepared in Comparative Example 2.

[0015] Figure 2 These are transmission electron microscope photos of strontium titanate crystals and amorphous oxygen-deficient strontium titanate generated by In doping.

[0016] Figure 3 This is a transmission electron microscope photograph of the amorphous oxygen-deficient strontium titanate generated by Zn doping prepared in Example 7.

[0017] Figure 4 It is the XRD spectra of strontium titanate crystal and amorphous oxygen-deficient strontium titanate.

[0018] Figure 5 This is a test chart of the photocatalytic degradation performance and stability of tetracycline by strontium titanate crystals and amorphous oxygen-deficient strontium titanate.

[0019] Figure 6 Electron spin resonance spectra of strontium titanate crystals and amorphous oxygen-deficient strontium titanate.

[0020] Figure 7 It is the nitrogen adsorption-desorption curve of strontium titanate crystal and amorphous oxygen-deficient strontium titanate.

[0021] Figure 8 This is the solid fluorescence spectrum of strontium titanate crystals and amorphous oxygen-deficient strontium titanate. DETAILED DESCRIPTION

[0022] Example 1 Preparation method of amorphous oxygen-deficient strontium titanate: first, dissolve 1 mL of isopropyl titanate in 25 mL of ethylene glycol to obtain solution A; then dissolve 3.9 mmol of strontium acetate and 2.3 mmol of indium nitrate in 25 mL of deionized water to obtain solution B; then, under magnetic stirring, add solution A dropwise to solution B, stir for 30 min, add 0.20 g of NaOH to the above solution, stir for 30 min, then place the mixed solution in a reactor and hydroheat at 160°C for 20 h. After cooling to room temperature, wash it alternately with deionized water and ethanol for 2 to 3 times, and dry it at 80°C to obtain amorphous oxygen-deficient strontium titanate. The transmission electron microscope photo of the amorphous oxygen-deficient strontium titanate generated by In doping prepared in Example 1 is shown in FIG. Figure 2 As shown in d-2f.

[0023] Example 2 The preparation method and process parameters of amorphous oxygen-deficient strontium titanate are the same as those in Example 1, except that the amount of indium nitrate is 1 mmol.

[0024] Example 3 The preparation method and process parameters of amorphous oxygen-deficient strontium titanate are the same as those in Example 1, except that the amount of indium nitrate is 4 mmol.

[0025] Example 4 First, 1 mL of isopropyl titanate was dissolved in 15 mL of ethylene glycol to obtain solution A; then 3.9 mmol of strontium acetate and 2.3 mmol of indium nitrate were dissolved in 15 mL of deionized water to obtain solution B; then, solution A was added dropwise to solution B under magnetic stirring, and stirred until solution A was evenly dispersed in solution B. 0.20 NaOH was added to the above solution and stirred for 30 minutes. Then, the mixed solution was placed in a reactor and hydrothermal at 180°C for 6 hours. After cooling to room temperature, it was washed alternately with deionized water and ethanol for 3 times, and dried at 60°C to obtain amorphous oxygen-deficient strontium titanate.

[0026] Example 5 First, 1 mL of isopropyl titanate was dissolved in 35 mL of ethylene glycol to obtain solution A; then 3.9 mmol of strontium acetate and 2.3 mmol of indium nitrate were dissolved in 15 mL of deionized water to obtain solution B; then, solution A was added dropwise to solution B under magnetic stirring, and stirred until solution A was evenly dispersed in solution B. 0.10 NaOH was added to the above solution and stirred for 30 minutes. Then, the mixed solution was placed in a reactor and hydrothermal at 160°C for 6 hours. After cooling to room temperature, it was washed alternately with deionized water and ethanol twice, and dried at 70°C to obtain amorphous oxygen-deficient strontium titanate.

[0027] Example 6 The preparation method and process parameters of amorphous oxygen-deficient strontium titanate are the same as those in Example 1, except that the hydrothermal reaction time is 15 hours. When the indium nitrate is unevenly dispersed or the NaOH is not fully dissolved, ultrasonic treatment is performed for 10 to 90 minutes.

[0028] Example 7 First, 1 mL of isopropyl titanate was dissolved in 35 mL of ethylene glycol to obtain solution A; then 3.9 mmol of strontium acetate and 2.3 mmol of zinc acetate were dissolved in 35 mL of deionized water to obtain solution B; then, under magnetic stirring, solution A was added dropwise to solution B, and stirred until solution A was evenly dispersed in solution B. 0.20 g of NaOH was added to the above solution, and stirred for 30 min. Then, the mixed solution was placed in a reactor and hydrothermal at 160°C for 20 h, and washed alternately with deionized water and ethanol for 3 times, and dried at 80°C. The transmission electron microscopy photo of the amorphous oxygen-deficient strontium titanate doped with Zn prepared in Example 7 is shown in FIG. Figure 3 shown.

[0029] Example 8 First, 1 mL of isopropyl titanate was dissolved in 25 mL of ethylene glycol to obtain solution A. Then, 3.9 mmol of strontium acetate and 2.3 mmol of zinc acetate were dissolved in 35 mL of deionized water to obtain solution B. Then, under magnetic stirring, solution A was added dropwise to solution B and stirred until solution A was evenly dispersed in solution B. 0.20 g of NaOH was added to the above solution and stirred for 30 min. Then, the mixed solution was placed in a reactor and hydroheated at 180 °C for 20 h, washed alternately with deionized water and ethanol for 2 to 3 times, and dried at 80 °C.

[0030] Example 9 The preparation method and process parameters of amorphous oxygen-deficient strontium titanate are the same as those in Example 7, except that the amount of zinc acetate is 4 mmol.

[0031] Example 10 The preparation method and process parameters of amorphous oxygen-deficient strontium titanate are the same as those in Example 7, except that the amount of zinc acetate is 1 mmol.

[0032] Comparative Example 1 Preparation of strontium titanate crystals: First, dissolve 1 mL of isopropyl titanate in 25 mL of ethylene glycol to obtain solution A; then dissolve 3.9 mmol of strontium acetate in 25 mL of deionized water to obtain solution B; then, under magnetic stirring, add solution A dropwise into solution B, stir for 30 min, add 0.20 g of NaOH to the above solution, stir for 30 min, then place the mixed solution in a reactor and hydroheat at 160°C for 20 h. After cooling to room temperature, wash it alternately with deionized water and ethanol for 2 to 3 times, and dry it at 80°C to obtain strontium titanate crystals.

[0033] The transmission electron microscope photo of the strontium titanate crystal prepared in Comparative Example 1 is as follows: Figure 2 a-2c. Figure 2 It can be seen from ab that the size of the strontium titanate crystal is between 100 and 300 nm, and its 0.275 nm lattice fringes correspond to the (110) crystal plane of strontium titanate. Figure 2 Clear light spots can be seen in the selected area diffraction photo of c, proving that strontium titanate has good crystallinity.

[0034] The transmission electron microscope photo of the amorphous oxygen-deficient strontium titanate prepared in Example 1 is as follows: Figure 2 d-2f. Figure 2 As can be seen in d, after adding indium nitrate, the sample has a loose porous structure and its size increases by nearly one-fold. This helps to increase the specific surface area and reactive sites; from the high-resolution transmission electron microscopy photo in 2e, it can be seen that after indium doping, strontium titanate has no obvious lattice fringes. Figure 2 There is no obvious light spot in the selected area diffraction pattern of f, indicating that amorphous oxygen-deficient strontium titanate has been formed. Figure 2 As shown in Figure g, through element mapping analysis, it is found that the four elements Sr, Ti, O, and In are evenly distributed on the catalyst surface. However, it can be seen that the In content is very low. Therefore, the main role of indium nitrate in the preparation process of strontium titanate is to interfere with the nucleation and growth of strontium titanate in the form of doping, thereby changing strontium titanate from a crystal to an amorphous structure.

[0035] Using the same method, we characterized the morphology and structure of the amorphous oxygen-deficient strontium titanate prepared in Example 7. Figure 3 It can be seen that adding an appropriate amount of zinc acetate during the preparation of strontium titanate can also affect the nucleation and growth of strontium titanate, thereby obtaining amorphous strontium titanate. Therefore, adding transition metal salts to the growth process of strontium titanate may be a universal method for preparing amorphous strontium titanate.

[0036] Figure 4 a is an XRD picture of the In-doped amorphous oxygen-deficient strontium titanate photocatalyst prepared in Example 1 and the strontium titanate crystal photocatalyst prepared in Comparative Example 1; Figure 4 b is the XRD images of the Zn-doped amorphous oxygen-deficient strontium titanate photocatalyst prepared in Example 7 and the strontium titanate crystal photocatalyst prepared in Comparative Example 1. It can be seen from the figure that after adding indium nitrate or zinc acetate, the diffraction peak position of strontium titanate remains basically unchanged, but the peak intensity becomes weaker, which is mainly because strontium titanate changes from a crystalline phase to an amorphous structure.

[0037] Comparative Example 2 A Chinese patent with application number 202211027698.7 discloses an experimental method for preparing amorphous nickel titanate by a hydrothermal method. The applicant referred to the experimental steps of the patent and replaced the nickel salt with a strontium salt. The obtained strontium titanate has a crystalline structure rather than amorphous oxygen-deficient strontium titanate.

[0038] Figure 1 The XRD, transmission electron microscope and selected area electron diffraction photos of the strontium titanate crystal prepared in Example 2 are shown. Figure 1 As shown, it can be seen from the XRD spectrum that the XRD peak of strontium titanate prepared by this method is strong, the half-peak width is very narrow, and the crystallinity is good. In addition, the lattice of strontium titanate can be clearly seen from the high-resolution transmission electron microscope photo, where the lattice with a lattice spacing of 0.276 nm corresponds to the (110) crystal plane of strontium titanate. Clear light spots can also be seen in the selected area diffraction image, indicating that the Chinese patent with application number 202211027698.7 is only applicable to the preparation of amorphous nickel titanate. Since strontium and nickel do not belong to the same family and have large differences in properties, the method in this patent is not applicable to the preparation of amorphous strontium titanate.

[0039] Photocatalytic experiment 35 mg of each of the amorphous oxygen-deficient strontium titanate photocatalyst prepared in Examples 1 to 3 and the strontium titanate crystal photocatalyst prepared in Comparative Example 1 were added to a quartz reaction cell, and 50 mL of deionized water and 10 mg of tetracycline (TC) were added and stirred for 30 min in the dark state to achieve efficient adsorption of TC by the catalyst. After turning on the light, 1 mL of the sample was taken every 30 minutes, and 1 mL of the above solution was filtered with a syringe using a 0.45 μm filter membrane. The change in TC concentration was detected by high performance liquid chromatography (XDB-C18 column, 250 mm × 4.6 mm, diode array detector).

[0040] like Figure 5 As shown in a-5b, under the irradiation of a 300 W xenon lamp, the degradation rate of TC by SrTiO3 crystals was 60% within 60 min, while the addition of 2.3 mmol indium nitrate to generate amorphous oxygen-deficient strontium titanate increased the degradation rate to 85%; after adding 2.3 mmol zinc acetate, the degradation efficiency increased to 82%, indicating that amorphous strontium titanate has better tetracycline degradation activity.

[0041] In addition to high photocatalytic activity, amorphous oxygen-deficient strontium titanate catalysts also have excellent pH universality and photocatalytic stability. Figure 5As shown in Figure c, after four photocatalytic cycles, under different tetracycline solution pH environments, namely alkaline (pH = 9), neutral (pH = 7), acidic (pH = 1), and finally alkaline (pH = 13), the photocatalytic activity did not change significantly. This shows that amorphous strontium titanate has a wide pH application range and can degrade tetracycline wastewater at various pH levels.

[0042] XPS was further used to characterize the stability of the samples before and after photocatalysis. Figure 5 d It can be seen that after 4 cycles, the peak positions and intensities of Sr, Ti, and O elements of the amorphous oxygen-deficient strontium titanate photocatalyst did not change significantly, indicating that the catalyst has good catalytic stability and structural stability.

[0043] Figure 6 The electron paramagnetic resonance spectra of the strontium titanate crystal prepared in comparative example 1 and the amorphous oxygen-deficient strontium titanate prepared in examples 1 and 7 are shown. Among them, the diffraction peak at the position of g=0.002 corresponds to the oxygen defect. It can be seen that the amorphous oxygen-deficient strontium titanate contains abundant oxygen defects, which can provide abundant surface active sites for the photocatalytic process and improve the photocatalytic activity.

[0044] Figure 7 The nitrogen adsorption-desorption curves of the strontium titanate crystals prepared in Example 1 and the amorphous strontium titanate prepared in Example 1 and Example 7 are used to detect the specific surface area of ​​the catalyst. Figure 7 It can be seen that the specific surface area of ​​amorphous oxygen defect strontium titanate is significantly higher than that of strontium titanate crystals. When the addition amount of indium nitrate is 2.3 mmol, the specific surface area increases from 377.4138 m 2 / g increased to 699.2318 m 2 / g. When the addition amount of zinc acetate is 2.3 mmol, the specific surface area increases from 377.4138 m 2 / g increased to 1181.8832 m 2 / g, the increase in specific surface area can increase the reactive sites and improve the adsorption capacity of tetracycline molecules.

[0045] Figure 8 It is the fluorescence spectra of the strontium titanate crystal prepared in comparative example 1 and the amorphous oxygen-deficient strontium titanate prepared in examples 1 and 7. It can be seen from the figure that the fluorescence intensity of the amorphous oxygen-deficient strontium titanate is significantly weaker than that of the strontium titanate crystal. This is because the fluorescence is generated by the recombination of electrons and holes. Therefore, the weaker fluorescence intensity of the amorphous oxygen-deficient strontium titanate proves that it has better carrier separation performance.

[0046] That is, adding indium nitrate or zinc acetate during the preparation of strontium titanate will affect the nucleation and growth of strontium titanate, transforming strontium titanate crystals into amorphous oxygen-deficient strontium titanate, thereby bringing the following benefits: (1) Stability: The structure and chemical properties of amorphous oxygen-deficient strontium titanate are very stable, and structural stability is a necessary condition to ensure the stability of photocatalytic performance. (2) Carrier transport performance: Amorphous oxygen-deficient strontium titanate can promote the separation and transport of carriers. (3) Active site: After the introduction of indium nitrate or zinc acetate, the surface structure of strontium titanate becomes loose and porous, thereby increasing the specific surface area and the number of reactive active sites. In addition, the addition of indium nitrate or zinc acetate introduces more surface defects to strontium titanate, which can serve as active centers for photocatalytic reactions and improve photocatalytic activity.

[0047] The present invention successfully prepares amorphous oxygen-deficient strontium titanate photocatalyst with high specific surface area, high performance and high stability by a simple hydrothermal method, which is simple to operate and novel in structure; the introduction of indium nitrate or zinc acetate effectively improves the specific surface area, the number of active sites and the carrier transport performance of strontium titanate; in addition, the introduction of indium nitrate or zinc acetate also improves the stability of strontium titanate. Therefore, the activity of photocatalytic degradation of tetracycline is significantly improved, the catalyst has good structural stability, and has the advantages of being green, environmentally friendly, low-consumption, high-efficiency and having good industrial prospects.

[0048] The above is only a preferred embodiment of the present invention. It should be pointed out that for those skilled in the art, several changes and improvements can be made without departing from the overall concept of the present invention, which should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing amorphous oxygen-deficient strontium titanate, characterized in that: The specific steps include: First, 1.0 mL of isopropyl titanate was dissolved in 15-35 mL of ethylene glycol to obtain solution A. Then, 3.9 mmol of strontium acetate and 1-4 mmol of indium nitrate or zinc acetate were dissolved in 15-35 mL of deionized water to obtain solution B. Then, under magnetic stirring, solution A was added dropwise to solution B, and stirred until solution A was evenly dispersed in solution B. 0.10-0.30 g of NaOH was added to the above solution, and stirred until it was completely dissolved. Then, the mixed solution was placed in a reactor and hydroheated at 160-180°C for 6-20 h, then cooled to room temperature, washed and dried.

2. The method for preparing amorphous oxygen-deficient strontium titanate according to claim 1, characterized in that: When indium nitrate or zinc acetate is not evenly dispersed or NaOH is not fully dissolved, ultrasonic treatment is performed for 10 to 90 min.

3. The method for preparing amorphous oxygen-deficient strontium titanate according to claim 1, characterized in that: The drying temperature is 60~80℃.

4. The method for preparing amorphous oxygen-deficient strontium titanate according to claim 1 is characterized in that the washing is performed by alternating deionized water and ethanol for 2 to 3 times.

5. An amorphous oxygen-deficient strontium titanate, characterized in that Prepared by the method according to any one of claims 1 to 4.

6. Application of amorphous oxygen-deficient strontium titanate, characterized in that: Amorphous oxygen-deficient strontium titanate for photocatalytic degradation of tetracycline.

Citation Information

Cited By

  • Aza-carbon-coated hollow porous structure strontium titanate and preparation method thereof

    CN117225451A

  • Nitrogen-doped carbon-coated hollow porous strontium titanate and its preparation method

    CN117225451B